Representations of the National Health Service (NHS) in UK print media. (4th June 2020) - Walker, Carl; Hanna, Paul; Raisborough, Jayne
Abstract: Generating negative news coverage of state welfare provision has been identified as a strategy designed to create public support for radical policies aimed to reduce such provision. To date, research of this kind has focused on scandals and crises. However, little is known about the complex relationship between media representations of specific events, and those of media representations in the lead up to these events, what we refer to as periphery representations. Employing a content and frame analysis, this paper analyses the frequency and intensity of peripheral representations of the National Health Service (NHS) in the British print media for 1 week a month before and for 1 week during three key events in recent NHS history: the official consultation period for the Health and Social Care Act; the publication of Five-Year Forward View, and the first Junior Doctor Strike. This article finds that negative NHS representations in articles that are peripheral to particular topical issues of controversy evidence fluctuations, amplifications and intensities across time periods, depending on the particular context. The paper concludes by arguing that repetition of negative themes in news helps to build a sensibility of 'inadequacy' of vital services. We hope that this focus on the ways in which amplifications and de-amplifications in negative intensity of peripheral NHS representations across time and content, helps to contribute to debate about the complex interplay between public health services, media representation and policy consent.